Karateristik Fisik Bunga Cengkeh (Syzygium aromaticum) - Miftahul Jannah; Junaedi Muhidong; Mursalim Mursalim (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2020)
Clove (Syzygium aromaticum), belongs to the Myrtaceae family and is one of Indonesia's native spice plants originating from the Maluku Islands. Clove post-harvest handling at the farm level is still done manually, one of which is the separation of flowers from the stems that are still using their hands. Flowers and clove stems need to be separated because they have different prices and qualities. The purpose of this study was to determine the attachment of cloves to their stems and physical characteristics (dimensions, weight and moisture content) of clove flowers in the varieties of Zanzibar, Si-Putih and Si-Kotok. Adhesiveness is intended as the force needed to release the clove flower from the stem so that it can be a reference and basic reference in the design of the clove flower separator from the stem or other processing equipment. This study used samples of clove flower varieties of Zanzibar, Si-Putih and Si-Kotok based on the color of the flower (level of maturity). The results of this study indicate that the adhesiveness of the clove Si-Kotok variety is 0.22 kg, the Zanzibar variety is 0.17 kg and the Si-Putih variety is 0.15 kg. In terms of color, the adhesiveness of red clove flowers is 0.22 kg, red green is 0.17 kg and green is 0.16 kg. The adhesiveness of cloves does not have a consistent correlation with the parameters of the physical properties of cloves.